The social institutions of capitalism : evolution and design of social contracts - Oosterhout, Hans van, 1965-; Heugens, Pursey; Vromen, Jack J., 1958- (Cheltenham, UK ; Northampton, MA : Elgar, 2003)
This book illustrates how social contracts necessarily underlie and facilitate all forms of capitalist production and exchange.
Includes bibliographical references and index.
osa 17/01/14
Loans
Keywords: Capitalism; Social contract